Sifat Pragmatis Partikel Lah dalam Kalimat Perintah - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
The study of the use of particles “lah” in command phrases in some references is always